The Active Role of Youth in Conservation of the Environment from the Perspective of Law No.40 of 2009 in Sei Kera Hilir 2 Sub-District Medan Perjuangan Kota Medan - Hadi Wardhana; Erika Revida; Sakhyah Asmara (PT FORMOSA CENDEKIA GLOBAL, 2022)
The environment is a space for life in all aspects whose natural nature is to provide the greatest benefit to humans. However, today's environmental conditions, especially in the city of Medan, are still not ideal. Various environmental problems that occur cause the benefits of the environment that should be obtained by the people of Medan City to be hampered. The contradiction between the ideal conditions of the environment and the objective conditions of the environment today requires the role of the community, especially youth, in environmental conservation, including the role of youth in environmental conservation in Sei Kera Hilir 2 Village, Medan Perjuangan District.This study aims to analyze the role of youth in environmental conservation efforts in Sei Kera Hilir 2 Subdistrict MedanPerjuangan based on Law No. 40 of 2009 Article 17 paragraph 1 regarding the active role of youth, to analyze what obstacles are experienced by youth in playing a role in environmental preservation in Sei Village. Kera Hilir 2, Medan Struggle District, to analyze the impact of the implementation of Law No. 40 of 2009 Article 17 on the role of youth in environmental conservation efforts in Sei Kera Hilir 2 Village, Medan Struggle District.